2018
DOI: 10.1111/jbi.13481
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian spatio‐temporal reconstruction reveals rapid diversification and Pleistocene range expansion in the widespread columnar cactus Pilosocereus

Abstract: Aim Pilosocereus is one of the richest and most widespread genera of columnar cacti, extending from south‐west USA to southern Brazil. Most species occur in the seasonally dry tropical forest biome but can also be found in xeric microhabitats inside woody savannas (Cerrado) and moist forests (Brazilian Atlantic forest). The genus exhibits a highly disjunct distribution across the Neotropics. Using a 90% complete species‐level phylogeny, we reconstructed the spatio‐temporal evolution of Pilosocereus to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 56 publications
5
42
1
2
Order By: Relevance
“…Historical biogeographic reconstructions were performed under a biogeographic event‐based model that considers both vicariance and dispersal as processes, DEC (Ree et al, ). The Bayesian implementation of this model (Landis, Matzke, Moore, & Huelsenbeck, ), in RevBayes (Höhna et al, ), has been used for testing different biogeographic scenarios (Lavor, Calvente, Versieux, & Sanmartin, ). We used species distributions categorized into the three RES, as delimited from beta diversity patterns (A, Atlantic; EP, East Pacific; and IWP, Indo‐West Pacific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historical biogeographic reconstructions were performed under a biogeographic event‐based model that considers both vicariance and dispersal as processes, DEC (Ree et al, ). The Bayesian implementation of this model (Landis, Matzke, Moore, & Huelsenbeck, ), in RevBayes (Höhna et al, ), has been used for testing different biogeographic scenarios (Lavor, Calvente, Versieux, & Sanmartin, ). We used species distributions categorized into the three RES, as delimited from beta diversity patterns (A, Atlantic; EP, East Pacific; and IWP, Indo‐West Pacific).…”
Section: Methodsmentioning
confidence: 99%
“…Bayesian implementation of this model (Landis, Matzke, Moore, & Huelsenbeck, 2013), in revbayes (Höhna et al, 2016), has been used for testing different biogeographic scenarios (Lavor, Calvente, Versieux, & Sanmartin, 2018). We used species distributions categorized into the three RES, as delimited from beta diversity patterns (A, Atlantic; EP, East Pacific; and IWP, Indo-West Pacific).…”
Section: Number Of Monophyletic Clades and Species Prunedmentioning
confidence: 99%
“…4). Likewise, other cacti, such as Harrisia and Pilosocereus show the same pattern (Franck et al, 2013b; Lavor et al, 2019), as do a wide range of other widespread tropical species that can be found naturally in south Florida and which are shared with the Caribbean (Long, 1974; Myers et al, 2000; Negrón‐Ortiz and Watson, 2003; Santiago‐Valentín and Olmstead, 2004). Some animals show the same pattern, such as the short‐faced bats, which initially diversified in the Caribbean before dispersing to continental North and South America (Dávalos, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Glacial and interglacial events during the Pleistocene are well known for their global effects on speciation and diversification in many organisms, especially plants (Stebbins, 1950, 1971; Simpson, 1975; Gentry, 1982; Prance, 1982; Pennington et al, 2004; Soltis et al, 2006; Rull, 2008; Ellison et al, 2012). Pleistocene fluctuations have also been suggested to have affected diversification in numerous groups of cacti from both North and South America, including some Antillean taxa (Majure et al, 2012; Ornelas and Rodriguez‐Gómez, 2015; Menezes et al, 2016; Perez et al, 2016; Franco et al, 2017; Lavor et al, 2019). In particular, the genus Harrisia shows a clear Caribbean radiation possibly originating in western Cuba that likely corresponds to the mid‐Pleistocene transition (Franck et al, 2013a) very similar to the pattern seen here in Consolea .…”
Section: Discussionmentioning
confidence: 99%
“…The fast and recent radiation in Barbacenia during the Neogene is likely associated with Miocene cooling (Zachos et al, 2008) and the expansion of rocky outcrops and the diversification of its flora (Alcantara et al, 2018, Antonelli et al, 2010, Arakaki et al, 2011, Lavor et al, 2019, Luebert and Wen, 2008, Perret et al, 2012, Särkinen et al, 2012. Besides, paleovegetation dynamics of Pleistocene and global climatic oscillations may have contributed to shaping the current diversity and distribution of Barbacenia lineages (Alcantara et al, 2018).…”
Section: One Of the Clades Comprised Only Endemic Species From Brazilmentioning
confidence: 99%